The impact of isoniazid preventative therapy and antiretroviral therapy on tuberculosis (TB) in HIV-infected children in a high TB incidence setting - Frigati, Lisa Jane (Department of Paediatrics and Child Health, 2014)
The aim of this study is to investigate the combined effect of IPT [INH preventative therapy] and ART [antiretroviral therapy] on TB incidence in HIV-infected children. A cohort analysis will be performed using data from a prospective, double-blinded placebo controlled trial of INH versus placebo in HIV-infected children in Cape Town, South Africa.